Leveraging social entrepreneurship for sustainable community development: A case study of community-based waste management in Indonesia - Sri Nurhayati; Wulan Tini (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
This study examines the role of social entrepreneurship in promoting sustainable community development through community-based waste management initiatives. Despite growing interest in social enterprises, limited empirical evidence exists on how technology-driven approaches contribute to environmental, economic, and social outcomes at the community level. Using a qualitative case study design, this research investigates Bank Sampah Bersinar Baleendah in Indonesia. Data were collected through semi-structured interviews, participant observation, and analysis of organizational documents, and analyzed using thematic analysis. The findings indicate that social entrepreneurial practices have contributed to transforming waste management into an economically viable and socially inclusive activity. The integration of hydrothermal technology has enhanced local employment opportunities, strengthened social cohesion, and increased environmental awareness. These findings highlight the role of technology-driven social enterprises as catalysts for sustainable development at the community level. This study contributes to the literature by providing empirical insights into how social entrepreneurship can integrate environmental sustainability with socio-economic development in emerging contexts.